A New Disaster Aid Information System Model for Indonesia Red Cross: A Case Study in East Java Province - Gede A WIDYADANA; Djoni H Setiabudi; Vivi Harsono; Randy Christian Wongso (International Journal of Supply Chain Management, 2018)
Humanitarian logistics is a complex system since there are many individuals and institutions should collaborate when a disaster happen. Therefore a good information system will be developed in this research to make the funding and distribution process efficient and effective. The model is developed based on a survey to 101 individuals in Surabaya, East Java, Indonesia to know their perception about humanitarian aids. The information model is developed for Indonesia Red Cross since this institution is the most trustworthy institution but only few respondents have donated their donation through this organisation. The model is developed by incorporating convenience store chain since they are good in distribution channel and networking. The system model result in more efficient and effective distribution process.